ANALISIS LINGKUNGAN TEMPAT TINGGAL ANAK JALANAN DI KOTA PEKANBARU - Dewi, Deslin Pramudita (Jurnal Kajian Lingkungan, 2014)
Pekanbaru city as the central government has developed a very rapid development in various fields such as economy, trade, transportation, education, housing, and other businesses. Developments led to the population of the city has increased very rapidly. This increase in population if not properly managed can lead to problems later on both social and environmental issues for the government of Pekanbaru. One of them is the problem of street children. In this study took the formulation of the problem of the state of the neighborhood in the city of Pekanbaru street children, street children know the social environment, and the impact of social living environment and the behavior of street children street children The method used in this research is to interview techniques and observations made in some point of intersection of street children like SKA Mall, Ramayana Shopping Centre, Junction expectations highway, Lotus Road, Prince Road hidayat, and Mall Pekanbaru. From the results of research conducted in some point of the childs residence street known that the street children are still far from the residence eligibility standards in general, such as the lack of toilets, TPS (landfills), lighting. Judging from the social situation of street children can be drawn conclusion that the low education of street children and street children social behavior deviates from social circumstances. While the impact of the social environment where street children live and is divided into two effects: the effect of internal and exsternal. Internal impact is shown by the presence of maturation itself, has a strong physical and has a strong group of people around the street children. Faktro exsternal ditinjaukkan with the occurrence of mental retardation, lack of education, lack of understanding of the norms that apply to the detriment of their environment.Keyword : Perception, the state of the neighborhood, the social and environmental impact of the social environment on behavior.